A Review on Different Types Of Cancer - Kumar, Neeraj; Sharma, Archana; Khinchi, M. P.; Kuma, Chanchal; Singh, Surya Pratap (Asian Journal of Pharmaceutical Research and Development, 2017)
Cancer remains one of the leading causes of morbidity and mortality worldwide. More than 70% of all cancer deaths occurred in low- and middle-income countries. Deaths from cancer worldwide are projected to continue rising. Cancer is a major health burden worldwide by 2030, over 9 million cancer patients are assumed to die in developing countries from different types of cancers. Incidence of different types of cancers is increasing due to unhealthy life style. At present, lung cancer is most prevalent in Bangladeshi male whereas it is cancer cervix in female. The developing world is already burdened by cancers some of which are attributable to infectious diseases. These disparities in cancer risk combined with poor access to epidemiological data, research, treatment, and cancer control and prevention combine to result in significantly poorer survival rates in developing countries for a range of specific malignancies.